A Study on the Landscape of Work Integrated Learning (WIL) to Improve Graduate Work-Readiness - Un Milagro, Veeanta (Digital Repository of Theses, 2024)
Background This dissertation provides an overview of a comprehensive study on Work Integrated Learning (WIL) in Indian higher education, particularly focusing on IT sector's demand for skilled graduates. The study offers unique insights into the landscape of WIL, its theoretical underpinnings. It highlights the urgency of enhancing graduate work-readiness in India. It also highlights that collaborative efforts are needed between industries and universities and in order to bridge the gap between theoretical education and practical workplace requirements. Methods The study is characterised as Quantitative, Descriptive, Cross-sectional, Non-experimental, Analytical, Field Research" approach. This design is carefully tailored to investigate the existing landscape of Work Integrated Learning (WIL) concerning university-industry collaboration in AICTE-approved institutes offering undergraduate courses in Engineering/Technology in Bangalore, India. Results The findings and implications of the study, highlights the effectiveness of WIL in improving graduate work-readiness and the importance of university-industry collaboration. It proposes a phased UIG-WIL model for preparing students for the workforce but also identifies challenges such as lack of causality and representativeness. While the study underscores the promising potential of WIL in addressing employability challenges in India, it also emphasizes the need for ongoing research, innovation, and collaboration to realize this potential fully. By embracing the recommendations outlined in the study, India can foster a culture of innovation, collaboration, and continuous improvement, to ensure graduates are well-equipped to flourish in the dynamically changing global workforce.